Zonificación agroclimática: una estrategia de planificación para sistemas agrícolas y pecuarios en la Alta Guajira, Colombia - Araujo Carrillo, Gustavo Alfonso; Martínez Maldonado, Fabio Ernesto; Deantonio Florido, Leidy Yibeth; Gómez Latorre, Douglas Andrés (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2024)
One of the most important dry agroecosystems in Colombia is found in the northern Guajira region, which has native inhabitants (sociocultural aspect) and semiarid zones (ecological aspect). This condition has resulted in great vulnerability in agricultural production systems to adverse climatic events, which require large scale action. For example, the establishment of agroclimatic suitability zones are needed to access information, for decision-making. The aim of this study was to carry out agroclimatic zoning in the municipality of Uribia (La Guajira) for agricultural production systems and animal feed species. The criteria used to identify the agroclimatic suitability zones included: plant coverage present in the municipality, soil suitability, water storage under water stress, regular conditions found in the municipality, and an extreme water deficit event. The evaluated conditions showed variations in agroclimatic suitability during the periods January to April and August to November. During an extreme water-deficit event between August and November, the suitable area for the establishment of production systems with plant species (type C3 and C4) was smaller (77,000 ha) than in the period January to April (130,000 ha). The agroclimatic suitability categories in Uribia did not exhibit differences between the evaluated periods under average water-deficit conditions.